Penanganan Perdagangan Barang Impor Ilegal dalan Perfektif Penegakan Hukum pada Marketplace Indonesia - Dwiatmanto Dwiatmanto; Yoga Ata Thorik Faza (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
The development of e-commerce has brought about significant changes to the buying and selling of imported goods through various marketplace platforms in Indonesia. The presence of these systems has made it easier for the public to obtain products from abroad. However, this situation has also posed challenges in the form of an increase in the circulation of imported goods that enter and are marketed without complying with applicable legal provisions, such as customs requirements, business licensing, product quality standards, and tax obligations. The purpose of this study is to examine the legal regulations governing the trade of imported goods through marketplaces. The research method employed a normative legal approach utilizing the statute approach, the conceptual approach, and the case approach. Data were obtained through a literature review and then analyzed qualitatively through legal interpretation and deductive reasoning. The results of the study indicate that regulations concerning the trade of imported goods through marketplaces are established in various relevant legal instruments, particularly through electronic systems. Although this regulatory framework is in place, the enforcement of these laws still faces several challenges, such as the sheer volume of digital transactions requiring oversight, suboptimal coordination among relevant agencies, weak verification processes for business operator identities, and the complexity of monitoring cross-border transactions. Therefore, strategic measures are needed, including enhancing inter-agency synergy, developing an integrated monitoring system, making more optimal use of digital technology, and strengthening the responsibility of marketplace operators in verifying business actors and monitoring the products being marketed